PADAT KARYA PENGRAJIN SEPATU KULIT SEBAGAI SOCIOPRENEUR EMPOWERMENT DI DAERAH POGOT SURABAYA [LABOR INTENSIVE OF SKIN SHOE WORKERS AS SOCIOPRENEUR EMPOWERMENT IN POGOT SURABAYA] - Risca Ayu Rachmania; Nurleila Jum’ati; Ayu Asmaul Masruroh; Mutiara Sabrinda (Universitas Pelita Harapan, 2019)
Leather shoe is the main attraction for consumers to protect and support the fashion. Relating to its fact, Resi 86 Safety Shoes is a business that carries intensive labor system which profit based socio-preneur of local communities in Pogot Surabaya. The issues of leather shoe craftsmen community in Pogot Surabaya are business no innovation ability, difficulty in finding qualify leather raw materials, passively and conventionally marketing. With such of issues, a lot of shoe craftsmen in Pogot Surabaya move to another job as the main job while the leather shoes craftmen as side job. Resi 86 Safety Shoes educate people in Pogot area by choosing or selecting raw materials and leather quality type according to SNI standard, designing a custom pattern and provide e-commerce in order to expand the product marketing. The result of labor-intensive application as sociopreneurship are: 1) creating a new product innovation and developing the resource potential for partner because the custom system offere so that products are more innovative and creative, 2) providing high quality raw materials as the production capital 3) The products can be known by the public. Thus, as the economic turnaround, it is capable to move the economic potential that can be enjoyed by the various parties involved.